UNDERSTANDING ENTREPRENEURIAL INTENTIONS THROUGH THE THEORY OF PLANNED BEHAVIOR: A STUDY AMONG BACHELOR OF SCIENCE (HONS.) FOOD SERVICE MANAGEMENT WITH ENTREPRENEURSHIP (HM252) STUDENTS - Fauzi, Farahin Yasmin Ahmad; Zakaria, Noor Hayati; Zulkifly, Muhammad Izzat; Abdul Majid, Mohd Aliff; Arsat, Aliffaizi; Abd Majid, Hairul Nizwan (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
Entrepreneurship has emerged as a crucial element of national development strategies and higher education curricula worldwide. Recognizing this, Universiti Teknologi MARA (UiTM) introduced the HM252 program; Bachelor of Science (Hons.) Food Service Management with Entrepreneurship, to foster entrepreneurial mindsets among students. This study aims to examine the factors influencing Entrepreneurial Intention (EI) among HM252 students at UiTM Puncak Alam using the Theory of Planned Behavior (TPB) as the conceptual foundation. Specifically, the study investigates the impact of four independent variables namely Attitude, Subjective Norms, Perceived Behavioral Control, and Entrepreneurship Education on students’ EI. A quantitative, correlational research design was adopted, employing a structured questionnaire distributed via Google Forms. The sample consisted of 129 HM252 students selected through convenience sampling. Data analysis was conducted using SPSS Version 28, applying multiple linear regression to determine the collective and relative contribution of each predictor to EI. Findings revealed that all four factors significantly influenced students’ entrepreneurial intention, with Attitude emerging as the strongest predictor, followed by Perceived Behavioral Control and Subjective Norms, while Entrepreneurship Education showed a positive yet comparatively smaller effect. A key limitation of this study is the analytical scope, which did not fully examine potential interactions among predictors. Future research should expand the model and sampling coverage to strengthen generalizability and provide deeper insights. Overall, the study offers meaningful implications for educators and policymakers seeking to enhance entrepreneurial intention through targeted psychological and educational interventions in higher education.